IMPROVING THE FINANCING OF ENTREPRENEURIAL ACTIVITY (American Journal of Research in Humanities and Social Sciences, 2023)
The article reveals the features and characteristics of small business and private entrepreneurship, the system of financing small entrepreneurship, analyzes the financial support of small businesses and private entrepreneurship, and carries out a correlation analysis of the main indicators of small business. Based on the analysis, scientific proposals and practical recommendations for improving the financing of small business and private entrepreneurship have been developed.